A socio-technical system perspective on sustainable organizational effectiveness: a PRISMA systematic review - Ali, Noor Azman; Ahmad, Sajjad; Hamzah, Amer; Kashif, Muhammad; Reaz, Md (International Center for Research in Islamic Economics, 2020)
Background. In fast paced era of 21st century, attaining and maintaining organizational effectiveness is a challenging task for the leaders and strategists. This systematic review intended to assess the modes of achieving effectiveness, from the existing literature across various disciplines and backgrounds. Methods. Relevant literature was identified from EBSCO, Web of Science, Scopus and ScienceDirect from their start to June 2019. Studies were selected on the basis of their relevance to organizational effectiveness and its determinants, especially in relation to sustainability in contemporary age. A sociotechnical system perspective was opted while reviewing and discussing the effectiveness studies. Results. We identified 614 studies, of which 59 studies (12 countries) were used for the study. The study found various antecedents, predictors, barriers and outcomes of a sustainable organizational effectiveness. The study highlighted sociotechnical perspective introducing the social and technical subsystems in an organization, keeping in view the needs of industrial revolution 4.0. It was suggested that a synergy between social and technical subsystem may result in sustainable organizational effectiveness, effectiveness in context of higher education institutions. Conclusions. A synergy between social and technical subsystems leads to sustainable organizational.